The Influence Of Organizational Justice And Inclusive Leadership On Organizational Commitment Among Employees At PT Mitra Aneka Rezeki, Kubu Raya Regency - Dinda Regina; Irfan Mahdi (UNIVED Press, 2024)
This study explores the impact of Organizational Justice and Inclusive Leadership on Organizational Commitment. Using data from 127 respondents, multiple regression analysis was conducted to assess the relationships between these variables. The findings indicate a positive but weak correlation between Organizational Justice, Inclusive Leadership, and Organizational Commitment. While the combined effect of both variables is statistically significant, their individual impacts are not significant. The coefficient of determination (R²) reveals that only 6.1% of the variation in Organizational Commitment can be explained by Organizational Justice and Inclusive Leadership. These results suggest that other factors not included in the study may contribute to Organizational Commitment. The study highlights the importance of leadership and justice in organizations, but also calls for further research to explore additional variables that may influence employee commitment.